Pengaruh Kompos Sludge Terhadap Perbaikan Erodibiltas Ultisol - Wiskandar Wiskandar (Fakultas Pertanian, Universitas Syiah Kuala, 2006)
The effect of Sludge Compost On Improving Erodibilty UltisolABSTRACT. Research for evaluation of using compost on erodibility Ultisol have been done at the experiment station of Jambi University, Mandalo Darat, Jambi. The objective experiment to show the effect of compost sludge to improve erodibilty Ultisols. The experiment was arranged in a randomized completely block design with 3 replications. The treatment consist of four levels sludge i.e. 0 ton ha-1, 10 ton ha-1, 20 ton ha-1, 30 ton ha-1. The data were analyzed by analysis of variances and Duncan’s Multiple Range Test. The result showed that there were increasing of sludge, improving organic matter, permeability and decreace of soil erodibilty.